1989
DOI: 10.1152/jn.1989.61.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Membrane properties and synaptic responses of the guinea pig nucleus accumbens neurons in vitro

Abstract: 1. The membrane properties and synaptic responses of guinea pig nucleus accumbens neurons in vitro were studied with intracellular recording methods. 2. The population of neurons could be divided into groups of low (20-60 M omega, average 46.5 M omega) and high (60-180 M omega, average 96.5 M omega) input resistance. The resting membrane potential in both groups was approximately -70 mV. 3. Other membrane properties were quite similar in both groups. Inward rectification occurred at potentials more negative th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 0 publications
8
21
0
Order By: Relevance
“…In agreement with other studies (Chang and Kitai 1986;Uchimura et al 1989b) the HPSP can be identified as a GABAA receptor-mediated IPSP and the DPSP as a glutamate receptor-mediated EPSP. The EPSP component is likely to be due to monosynaptic activation considering its constant onset latency in spite of varying stimulation intensity.…”
Section: Postsynaptic Potentsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with other studies (Chang and Kitai 1986;Uchimura et al 1989b) the HPSP can be identified as a GABAA receptor-mediated IPSP and the DPSP as a glutamate receptor-mediated EPSP. The EPSP component is likely to be due to monosynaptic activation considering its constant onset latency in spite of varying stimulation intensity.…”
Section: Postsynaptic Potentsupporting
confidence: 92%
“…This observation is in agreement with the slow rise time of NMDA receptormediated activity recorded in cultured neurons from the hippocampus and the spinal cord (Forsythe and Westbrook 1988). Since low-affinity glutamate receptor antagonists were used in previous studies on synaptic responses in the ventral and dorsal striatum (Cordingley and Weight 1986;Cherubini et al 1988;Uchimura et al 1989b;Walsh et al 1989), the present investigations are the first to suggest that fast EPSPs evoked by local or callosal stimulation are almost completely mediated by Q/K receptors.…”
Section: Postsynaptic Potentsupporting
confidence: 90%
See 3 more Smart Citations